Fairness-Driven Model Auditing: Eliminating Socio-Algorithmic Bias in Large-Scale AI Deployments (Journal of responsible AI & ethics, 2026)
Artificial intelligence has become a fundamental decision-making agent in domains such as finance, healthcare, governance, recruitment, digital services, public policy, and cybersecurity. However, large-scale AI deployments increasingly expose systemic algorithmic biases that mirror or amplify real-world social inequalities. These biases are not purely computational anomalies but deeply socio-technical failures rooted in skewed data distributions, unequal representation, feedback loops, flawed labeling, proxy variables, cultural assumptions, and opaque model optimization objectives. This research critically evaluates frameworks for fairness-driven model auditing, proposing a reproducible large-scale bias identification pipeline built on disparate impact quantification, adversarial debiasing, counterfactual fairness testing, causal regression tracing, demographic parity validation, and algorithmic accountability matrices. A mixed-method evaluation was conducted involving: 7 AI deployment sectors, 42 trained models, 1.2 million decision records, 15 demographic identity attributes, 320 contributes to structured expert surveys, bias stress-testing pipelines, fairness performance indices, and socio-algorithmic harm simulations. Results indicate that un-audited high-scale models contain an average disparate outcome deviation of 31%, amplified misclassification errors for minority groups by 38–64%, and socially regressive feedback cycles in 72% of reinforcement-based systems. After fairness auditing, bias mitigation protocols improved equitable outcomes by 67%, reduced denial disparity by 53%, minimized demographic performance gap to